Long-Term Survival After Venous Thromboembolism: A Prospective Cohort Study - Nilius, Henning; Mertins, Tamara; Boss, Robin; Knuchel, Matthias; Blozik, Eva; Kremer Hovinga, Johanna Anna; Eichinger, Sabine; Nagler, Michael (Frontiers in Cardiovascular Medicine, 2021)
Background: Little is known about long-term survival after the initial treatment of venous thromboembolism (VTE). In a prospective cohort study, we aimed to assess the long-term mortality and key predictor variables relating to disease severity, treatment intensity, and comorbidities. Materials and Methods: Between 1988 and 2018, 6’243 consecutive patients with VTE from a University outpatient unit were prospectively included and followed until December 2019; clinical characteristics, measures of disease severity, and treatment details were recorded. Dates of death were retrieved from the Swiss Central Compensation Office. Results: Overall, 254 deaths occurred over an observation period of 57’212 patient-years. Compared to the Swiss population, the standardized mortality ratio was 1.30 (95% CI 1.14, 1.47; overall mortality rate: 4.44 per 1’000 patient-years). The following predictors were associated with increased mortality: Unprovoked VTE (hazard ratio [HR]: 5.06; 95% CI: 3.29, 7.77), transient triggering risk factors (HR: 3.46; 95% CI: 2.18, 5.48), previous VTE (HR 2.05; 95% CI: 1.60, 2.62), pulmonary embolism (HR: 1.45, 95% CI: 1.10, 1.89), permanent anticoagulant treatment (HR 3.14; 95% CI: 2.40, 4.12), prolonged anticoagulant treatment (7-24 months; HR 1.70; 95% CI: 1.16, 2.48), and cardiovascular comorbidities. Unprovoked VTE, previous VTE, permanent and prolonged anticoagulation remain independent risk factors after adjustment for age, sex, and comorbidities. Conclusion: Survival after VTE was significantly reduced compared to the Swiss general population, especially in patients with more severe disease, cardiovascular comorbidities, and longer anticoagulant treatment.